A model for public interest ethnography: the conjunction of theory, practice, action, and change in a globalizing world - Sanday, Peggy Reeves (Revista de Antropología Social, 2013)
This paper outlines a model for and the history of Public Interest Ethnography (PIE). The aim is to codify the means by which theory, practice, and action for change in a globalizing world can and has been knitted together by ethnographers adopting a micro ethnographic approach wedded to macro considerations. The term “public interest” refers both to broader interests related to the “common good” (the macro level) and to specific interests aired by actors in the public sphere of debate and action in any society (the micro level.) Engagement at these various levels catapults the ethnographer into the realm of shared understandings and struggle as contested interests vie for public attention. The major theme underlying the goal of PIE is to join ethnography to interpretation and change in the public domain.
Keywords: Public Interest; sociocultural anthropology; ethnography; engaged anthropology; engaged postmodern science; lexicon for public interest ethnography